THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION BAKSO SONHAJI SONY LAMPUNG - Nadia Putri Karenina; Maya Ariyanti (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
Based The food and beverage industry can survive and increase during the time of covid-19. The culinary sector is the largest contributor to PDB in the creative industry. In the midst of the people's weakening purchasing power, the contribution of Indonesian consumer spending on food spending is still the largest, because of this the culinary business in Indonesia continues to grow, one of which is in Lampung. Lampung has a variety of famous culinary. One of the legendary and famous culinary is Bakso Sonhaji Sony Lampung. Sales of Bakso Sonhaji Sony Lampung increased in 2019 - 2020, therefore, customer reviews also increased. There are positive reviews and not a few negative reviews and low ratings given by customers regarding products and services of Bakso Sonhaji Sony Lampung. This study aims to determine the effect of product quality and service quality on customer satisfaction Bakso Sonhaji Sony Lampung. The data collection technique used is primary data by distributing questionnaires using a Likert scale with 100 respondents. The method used in processing the data in this study is multiple linear regression using the SPSS (Statistical Program for Science) application. From the results of questionnaires and data processing, this study shows that product quality has a partial effect on customer satisfaction. service quality has a partial effect on customer satisfaction. There is a simultaneous influence on product quality and service quality on customer satisfaction.